Pendidikan Karakter Ulil Albaab dan Neurosains Spiritual dalam Mencegah serta Mengobati Adiksi Pornografi pada Pelajar Menengah - Waropun Ghofur; Didin Hafidhuddin; Akhmad Alim; Ibdalsyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The threat of pornography addiction among adolescents has evolved into a multidimensional crisis. Easy access to pornographic content in the digital revolution era increases exposure to repeated dopaminergic hyperstimulation. Recent clinical neuroscience literature explicitly links this condition to a disrupted reward system, weakened inhibitory control, and reduced volume in the prefrontal cortex (PFC). This study aims to formulate the Ulul Albab educational paradigm as a comprehensive preventive and curative framework for addressing pornography addiction through a transdisciplinary hybridization of Islamic character education, thematic Quranic exegesis, modern clinical neuroscience, and Islamic guidance and counseling based on Tazkiyatun Nafs (purification of the soul). Employing a qualitative approach based on library research and literature review, this study synthesizes empirical quantitative data from recent neuro-educational studies as secondary sources to contextualize the Quranic concept of Ulul Albab. The literature review indicates that a dialectical balance between spiritual awareness (Dhikr) and analytical acuity strengthens inhibitory control. In the curative dimension, the internalization of this character activates Nafs al-Lawwamah (the self-reproaching soul); neurobiologically, this correlates with moral guilt in the dorsomedial prefrontal cortex (dmPFC) and anterior cingulate cortex (ACC), thereby triggering Taubat Nasuha (sincere repentance). Structured spiritual practices—including the tripartite counseling method (Takhalli, Tahalli, Tajalli) and the Siyaq contextual memorization method—support spiritual neuroplasticity. This synthesis of literature demonstrates that faith-based character education is capable of rehabilitating neurotoxic damage resulting from digital addiction.